Glucocorticoid Induces Incoordination between Glutamatergic and GABAergic Neurons in the Amygdala - Wang, Guang-Yan (PLoS One, 2016)
BACKGROUND: Stressful life leads to mood disorders. Chronic mild stress is presumably major etiology for depression, and acute severe stress leads to anxiety. These stressful situations may impair hypothalamus-pituitary-adrenal axis and in turn induce synapse dysfunction. However, it remains elusive how the stress hormones mess up subcellular compartments and interactions between excitatory and inhibitory neurons, which we have investigated in mouse amygdala, a structure related to emotional states. METHODS AND RESULTS: Dexamethasone was chronically given by intraperitoneal injection once a day for one week or was acutely washed into the brain slices. The neuronal spikes and synaptic transmission were recorded by whole-cell patching in amygdala neurons of brain slices. The chronic or acute administration of dexamethasone downregulates glutamate release as well as upregulates GABA release and GABAergic neuron spiking. The chronic administration of dexamethasone also enhances the responsiveness of GABA receptors. CONCLUSION: The upregulation of GABAergic neurons and the downregulation of glutamatergic neurons by glucocorticoid impair their balance in the amygdala, which leads to emotional disorders during stress.